Hacking Muhammad Syahrûr's Hudûd Theory and Its Relevance to the Inheritance of Sangkolan Madurese People - Moh. Mujibur Rohman; Siti Muafatun (IAIN Manado, 2021)
Muhammad Syahrûr is a modern thinker from Damascus with the theory of hudûd or limits in interpreting the verses of the Qur'an (or al-Tanzîl al-Hakîm). One of the theoretical scopes offered is hâlah al-hadd al-adnâ wa al-hadd al-a'lâ mâ'an (minimum and maximum limits simultaneously) which he applies to the inheritance verse. Syahrûr in interpreting the inheritance verse is quite different from classical scholars. He considered classical scholars too rigid in interpreting the inheritance verse. At the same time, for Syahrûr the 2:1 concept would move dynamically according to the hudûd that God had determined in the inheritance verse. The research method used is normative-empirical with a qualitative approach. This study aims to relevance the theory of hudûd Muhammad Syahrûr with the practice of inheritance of the Madurese community in the form of sangkolan. The results of this study indicate that between Syahrûr's hudûd theory, there is relevance to the practice of Sangkolan inheritance of the Madurese community in realizing gender justice either individually (nadzrah al-fardiyah) or collectively based on majmû'at al-dzukûr and majmû'at al-inâts.